2009
DOI: 10.1098/rsbl.2009.0169
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and sexual size dimorphism in an Arctic spider

Abstract: Climate change is advancing the onset of the growing season and this is happening at a particularly fast rate in the High Arctic. However, in most species the relative fitness implications for males and females remain elusive. Here, we present data on 10 successive cohorts of the wolf spider Pardosa glacialis from Zackenberg in HighArctic, northeast Greenland. We found marked inter-annual variation in adult body size (carapace width) and this variation was greater in females than in males. Earlier snowmelt dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 21 publications
4
69
1
Order By: Relevance
“…For instance, earlier spring snowmelt and longer growing seasons are associated with larger adult body size in arctic spider species, particularly in females (Høye et al 2009;Høye & Hammel 2010). Large females have higher reproductive output, but increased sexual size dimorphism may also alter competition between males and females and thus affect survival.…”
Section: (B) Abiotic and Species Interactionsmentioning
confidence: 99%
“…For instance, earlier spring snowmelt and longer growing seasons are associated with larger adult body size in arctic spider species, particularly in females (Høye et al 2009;Høye & Hammel 2010). Large females have higher reproductive output, but increased sexual size dimorphism may also alter competition between males and females and thus affect survival.…”
Section: (B) Abiotic and Species Interactionsmentioning
confidence: 99%
“…In wolf spiders, Høye et al [24] found that both males and females increased in size in association with earlier snowmelt, but that females grew more. Here, we found the opposite; male AGS at Atigun, where spring conditions occur earlier, weighed less than Toolik males ( figure 7).…”
Section: (C) Body Sizementioning
confidence: 99%
“…Mismatches may also be created between sexes within a species if males and females use different cues to time their phenology or respond to climate change differently. Høye et al [24] found that earlier snowmelt increased adult body size in wolf spiders but with a skew towards positive sexual size dimorphism, which may have later effects on population dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…These studies follow up on earlier studies of body size variation in spiders collected in the same pitfall traps. In the High Arctic crab spider (Xysticus deichmanni Sørensen 1898), body size varied among habitats (Bowden et al 2015b), while in a more mobile wolf spider (Pardosa glacialis), body size was positively associated with interannual variation in the length of the growing season (Høye et al 2009). The pattern of temporal variation in wolf spider body sizes was corroborated by similar variation along an elevational gradient for two of three wolf spider species studied at Disko Island in West Greenland (Høye and Hammel 2010).…”
Section: Arctic Long-term Monitoringmentioning
confidence: 99%